Beta signal activity analysis using Power Spectra Density (PSD) algorithm with murrotal surah al-Fatihah stimulation on adolescent anxiety - Tika Rahmawati; Latifatul Istianah (Journal of Holistic Medical Technologies (JHMT), 2024)
Adolescence is a period of changes within adolescents, both physically and emotionally. According to the results of the Basic Health Research (Riskesdas) from the data of the Indonesian Ministry of Health, people over the age of 15 experience indications of anxiety around 14 million people. This figure is equivalent to 6% of the total population of Indonesia. This study aims to determine changes in Beta signals and measure adolescent anxiety in anxious conditions and after listening to the murottal letter Al-Fatihah. This study uses quantitative methods with an experimental approach. Respondents were students of Walisongo State Islamic University aged 17-21 years. This study used a KT88-type EEG device to measure respondents' brain waves and used the Zung Self-Rating Anxiety Scale (SAS/SRAS) questionnaire to measure anxiety. Respondents filled out the questionnaire when they were anxious, and then they were fitted with an EEG and listened to the murottal of Surah Al-Fatihah. The results of this study showed that the average beta wave decreased from 5.83% to 5.08% after listening to the murottal surat Al-Fatihah, and measurement using the SRAS questionnaire obtained an average score when anxious was 55.85, while when listening to the murottal the average was 36.7. It shows that murottal surat Al-Fatihah can reduce anxiety in adolescents.